Effects of transfusion with red cells filtered to remove leucocytes: randomised controlled trial in patients undergoing major surgery. Issue 7451 (13th May 2004) - van Hilten, Joost A; van de Watering, Leo M G; van Bockel, J Hajo; de Velde, Cornelis J H; Kievit, Job; Brand, Ronald; van den Hout, Wilbert B; Geelkerken, Robert H; Roumen, Rudi M H; Wesselink, Ronald M J; Gemert, Ankie W M M Koopman-van; Koning, Jan; et al.
Abstract: Objective To compare postoperative complications in patients undergoing major surgery who received non-filtered or filtered red blood cell transfusions. Design Prospective, randomised, double blinded trial. Setting 19 hospitals throughout the Netherlands (three university; 10 clinical; six general). Participants 1051 evaluable patients: 79 patients with ruptured aneurysm, 412 patients undergoing elective surgery for aneurysm, and 560 undergoing gastrointestinal surgery. Interventions The non-filtered products had the buffy coat removed and were plasma reduced. The filtered products had the buffy coat removed, were plasma reduced, and filtered before storage to remove leucocytes. Main outcome measures Mortality and duration of stay in intensive care. Secondary end points were occurrence of multi-organ failure, infections, and length of hospital stay. Results No significant differences were found in mortality (odds ratio for filtered v non-filtered 0.80, 95% confidence interval 0.53 to 1.21) and in mean stay in intensive care (- 0.4 day, - 1.6 to 0.6 day). In the filtered group the mean length of hospital stay was 2.4 days shorter (- 4.8 to 0.0 day; P = 0.050) and the incidence of multi-organ failure was 30% lower (odds ratio 0.70, 0.49 to 1.00; P = 0.050). There were no differences in rates of infection (0.98, 0.73 to 1.32). Conclusion The use of filtered transfusions in some types of major surgery may reduce the length of hospital stay and the incidence of postoperative multi-organ failure.